If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(u-2)-3=-5(-2u+2)-2u
We move all terms to the left:
2(u-2)-3-(-5(-2u+2)-2u)=0
We multiply parentheses
2u-(-5(-2u+2)-2u)-4-3=0
We calculate terms in parentheses: -(-5(-2u+2)-2u), so:We add all the numbers together, and all the variables
-5(-2u+2)-2u
We add all the numbers together, and all the variables
-2u-5(-2u+2)
We multiply parentheses
-2u+10u-10
We add all the numbers together, and all the variables
8u-10
Back to the equation:
-(8u-10)
2u-(8u-10)-7=0
We get rid of parentheses
2u-8u+10-7=0
We add all the numbers together, and all the variables
-6u+3=0
We move all terms containing u to the left, all other terms to the right
-6u=-3
u=-3/-6
u=1/2
| 64^x-1/16^2x+2=2^x-2 | | 4.7k+83=318 | | 55t-16t^2=0 | | 3+2=3c+2 | | 6x-2+2(4x+6)=-2(×+4) | | 118+p-18=180 | | 4x+12=9x+11 | | -2(4w-4)+2w=2+2(2w-1) | | 0x=42 | | 6x+3(3x13)=21 | | 2(w+5)=-4(5w-7)+6w | | /7(2x-8)=77x | | 1.50x+10=4x | | 30=t+7 | | 33+2z+z-6=180 | | -1/2w=-9 | | 2x+x-5+3x+5=180 | | -9x-26=-2(x+6) | | 7(u+3)=-7u-21 | | 23.4=6w | | 43/0.5=x | | 43/0.4=x | | 3(4+x)=13-5x | | 6=w/3 | | 3x+33=13x-17 | | 4/x=32/20 | | 8(x-13)=8(3x-11) | | 9^x-1*81^2x-1=27^3x-2 | | 3(6+x)=13-2x | | 6.50s+8.50=80 | | -1/3w+1=-7 | | 85/180=x/40 |